The Role of Mount Lawu Propolis in Modulating Oxidative Stress and Angiogenic Factors During the Proliferation Phase of Wound Healing - Muhammad Apri Rajab; Amru Sungkar; Ida Bagus Budhi Surya Adnyana (HM Publisher, 2025)
Background: The skin, the body's largest and first-line defense organ, is crucial for protection against environmental aggressors, thermoregulation, fluid balance, immune surveillance, sensory perception, and the intricate process of wound healing. This study investigated the modulatory role of Mount Lawu propolis extract on Malondialdehyde (MDA), a marker of oxidative stress, and Vascular Endothelial Growth Factor (VEGF), a key mediator of angiogenesis, during the critical proliferation phase of wound healing. Methods: A post-test-only control group design experimental study was conducted using twenty-four male rats (Rattus norvegicus). Following the creation of standardized full-thickness skin excision wounds, the rats were divided into four groups (n=6 per group): a control group receiving no propolis, and three treatment groups receiving topical applications of 200mg/kgBB (Group 1), 400mg/kgBB (Group 2), and 800mg/kgBB (Group 3) ethanol propolis extract daily for seven days. MDA and VEGF expression in granulated tissue samples were evaluated using immunohistochemistry and semi-quantitatively scored. Statistical analysis involved the Kruskal-Wallis non-parametric test, followed by the Mann-Whitney test due to non-normal data distribution. Results: MDA levels showed a significant reduction (p<0.05) in Group 2 (400mg/kgBB propolis) compared to the control, indicating a dose-specific antioxidant effect. VEGF expression demonstrated a significant increase (p<0.05) in all propolis-treated groups (Groups 1, 2, and 3) compared to the control, confirming the pro-angiogenic potential of propolis. Notably, the highest VEGF expression was observed in Group 3 (800mg/kgBB propolis). Conclusion: Mount Lawu ethanol propolis extract effectively modulated both oxidative stress and angiogenesis during the proliferation phase of wound healing in this rat model. A 400mg/kgBB/day dose of propolis optimally reduced MDA expression, while propolis at all doses, particularly 800mg/kgBB/day, significantly enhanced VEGF expression. These findings suggest propolis as a promising therapeutic agent to enhance wound healing by mitigating oxidative stress and promoting angiogenesis.